2021
DOI: 10.1038/s41598-020-78950-7
|View full text |Cite
|
Sign up to set email alerts
|

Origin of perpendicular magnetic anisotropy in amorphous thin films

Abstract: The emergence of perpendicular magnetic anisotropy (PMA) in amorphous thin films, which eventually transforms the magnetic spins form an in-plane to the out-of-plane configuration, also known as a spin-reorientation transition (SRT), is a fundamental roadblock to attain the high flux concentration advantage of these functional materials for broadband applications. The present work is focused on unfolding the origin of PMA in amorphous thin films deposited by magnetron sputtering. The amorphous films were depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…In addition, LiAlO 2 layers with thicknesses of 100 and 300 nm were also fabricated on the surface of lithium, as shown in Figure S2. XPS was used to characterize LiAlO 2 due to its amorphous nature Figure d shows the XPS results of the LiAlO 2 layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, LiAlO 2 layers with thicknesses of 100 and 300 nm were also fabricated on the surface of lithium, as shown in Figure S2. XPS was used to characterize LiAlO 2 due to its amorphous nature Figure d shows the XPS results of the LiAlO 2 layer.…”
Section: Resultsmentioning
confidence: 99%
“…XPS was used to characterize LiAlO 2 due to its amorphous nature. 31 Figure 2d shows the XPS results of the LiAlO 2 layer. The peak at 530.6 eV corresponds to the O 1s in LiAlO 2 (Figure 2e), and the peak at 55.1 eV, which is assigned to the Li 1s (Figure 2f) in the LiAlO 2 layer, is different than that of lithium metal (55.4 eV).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, for samples grown at 4.5 mTorr, a clear increase in H c followed by an earlier steep decrease is visible, indicative of a larger amount of AFM dragged spins. This effect may be due to higher local disorder at the interface as a consequence of higher deposition pressure [38]. In fact, Tang et al [24] showed that H ex depends strongly on the deposition atmosphere, reporting higher values when the pressure was lower.…”
Section: H Ex and T B Distribution For Different Mnir Growth Conditionsmentioning
confidence: 99%
“…Of particular interest is the design and fabrication of special nano-structured thin films, including magnetic layers, for the regulation of MOKE rotation inverse and the related reversal mechanism study. To date, various nanostructures, including periodic rectangular apertures [35], optical Tamm-state structures [36,37], and prism-coupled surface-plasmon-resonance systems [38,39], have been investigated to enhance sensing performance assisted by a variety of fabrication methods, such as electrochemical deposition [40,41] and magnetron sputtering [42].…”
Section: Introductionmentioning
confidence: 99%